Influence of Green Supply Chain Management Practices on Operational Performance: An Empirical Study amongst Pakistani Textile Manufacturers (Journal of Business Management and Accounting, 2019)
The purpose of the present research is to investigate the influence of green supply chain management practices on the operational performance of the textile manufacturing industry in Pakistan. The study analyzed three main determinants of green supply chain management practices, i.e., green purchasing, eco-design and environmental cooperation with customers. The study utilized a sample of 152 textile manufacturing organizations. The data was collected through survey method using a reliable and valid questionnaire. Statistical analysis was performed using the Partial Least Square Structural Equation Modelling technique with the aid of Smart PLS software version 3.0. Multiple regression analysis was employed for hypotheses testing. Empirical findings reveal a strong influence of green practices: eco-design and environmental cooperation with customers on increased operational performance of textile manufacturing organizations.